Evaluation of STAT5A Gene Expression in Aflatoxin B1 Treated Bovine Mammary Epithelial Cells - Ali Forouharmehr; Taher Harkinezhad; Babak Qasemi-Panahi (Tabriz University of Medical Sciences, 2013)
Purpose: Aflatoxin B1 (AFB1) is a potent mycotoxin which has been produced by fungi such as Aspergillus flavus and Aspergillus parasiticus as secondary metabolites due to their growth on food stuffs and induces hepatocellular carcinoma in many animal species, including humans. In the present study, the effect of AFB1 on STAT5A gene expression was investigated in bovine mammary epithelial cells using real time RT-PCR. Methods: Bovine mammary epithelial cells were seeded in a 24-well culture plate for three-dimensional (3D) culture in Matrigel matrix. After 21 days of 3D culture and reaching the required number of cells, cells were treated with AFB1 and incubated for 8 h. For real time PCR reaction, total RNA from the cultured and treated cells was extracted and used for complementary DNA synthesis. Results: The expression of STAT5A gene was significantly down regulated by AFB1 in dose- dependent manner and led to the reduction of proliferation and differentiation of epithelial cells, which has direct effect in milk protein quantity and quality. Conclusion: According to the results, it seems that down regulation of STAT5A gene in AFB1-treated cells maybe due to DNA damage induced by AFB1 in bovine mammary epithelial cells.